A tradicionalidade da ocupação indígena e a constituição de 1988: a territorialização como instituto jurídico-constitucional - Viegas, Daniel Pinheiro (2015)
This dissertation investigates the meaning of the expression traditionally occupied lands coined in the Federal Constitution of 1988 and interpreted by the Supreme Court in which the judgment of Petition no. 3388/RR in 2009, the case of the Raposa Serra do Sol Indigenous Land, founded on the theory of the indigenous fact (“fato indígena”), established the promulgation of the National Constitution as a timeframe for the recognition of indigenous territorial r ights. For this purpose, an initial inquiry on the history of the State's relationship with indigenous territorial rights in Brazil was carried out, based on the analysis of how Iberian States during the colonial period, and the Brazilian government established regulation of the relationship with Brazilian indigenous peoples and their territories, through legal frameworks. Then the entire construction process of the legal text of article 231, paragraph 1 of CRFB/88 from international debates on the ILO Convention No. 169 is analyzed, up to the discussions held in the National Constituent Assembly of 1987. I describe the survey of how the legal doctrine and jurisprudence of the Supreme Court came to interpret the legal text mentioned here. Given these documentary data, the research will examine the hypothesis that the Federal Constitution of 1988, in art. 231, §1º and article 215, §1º, going beyond the indigenato and indigenous fact, have established territorialization as a legal institution. To measure this hypothesis the research investigates the following issues: 1) Is the expression traditionally occupied lands “vague” and does it permit the application of the conception used by the Supreme Court? 2) Is it possible, through the theory of constitutional change, to admit that article 231, §1 of the 1988 Federal Constitution has altered its meaning to allow a time limitation for indigenous territorial rights? 3) Considering the relationship between indigenous and quilombola territorial law, how has the latter been achieved by case-law of the lower courts? 4) How do indigenous peoples interpret article 231, paragraph 1 of the 1988 Federal Constitution from the experiences of Northeast Indian demands and new urban conflicts in the North? 5) How to think about a traditionalism that is distant from archaeological and ethnocentric perspectives? 6) How to approach constitutionalizing attainment of article 231, § 1 of the Federal Constitution?